PENGARUH GREEN MARKETING, GREEN TRUST DAN GREEN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK TUPPERWARE DI KOTA BANYUWANGI - Rena Aviolina Fernanda; Rio Sudirman; Teguh Purnomo (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
The purpose of this study is to see whether Green Marketing, Green Trust and Green Brand image influence purchasing decisions. This research is quantitative using purposive sampling method with a sample size of 72 respondents. The results of hypothesis testing show the findings of purchasing decisions partially influenced by Green Marketing and Green Trust variables regardless of the green brand variable, but simultaneously the Green Marketing, Green Trust Green Brand image variables affect product purchasing decisions.